CFD simulation of bubbling fluidized bed: Effects of bed column geometry on hydrodynamics of gas–solid mixing: Numerische Strömungssimulation einer blasenbildenden Wirbelschicht: Einfluss der Reaktorgeometrie auf die hydrodynamischen Eigenschaften einer Gas-Feststoff Mischung - Afrooz, I.E. (Wiley-VCH Verlag, 2017)
In this study, multiphase computational fluid dynamics (CFD) is employed to simulate and study the hydrodynamics behavior of gas-solid mixing in a new bed column design of bubbling fluidized bed called swirl bed. The new fluidized bed is a swirl tube reactor design based on swirl tube technology. The results are compared with the conventional straight tube rector which is the scaled down version of the existing pilot plant gasifier. It is found that the usage of the swirl tube reactor design results in better lateral solid mixing inside the bed. Furthermore an increase in residence time of the particles is also observed due to the swirl motion of the particles. © 2017 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim